Escalation of Political Conflict in the Management of the West Sumatera Hanura Party Regional Representative Council - Akmal Arianto; Aidinil Zetra; Tengku Rika Valentina (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2021)
This research discusses the political conflict in managing the Regional Executive Board ofHanura Political Party in West Sumatera. The method used in this research is a qualitative approach withdescriptive type. The theory used in this research is the theory of conflict-causing factors from SimonFisher and the concept of political conflict from Ramlan Surbakti. From the research that was conducted,it was found that some factors caused the political conflicts. Firstly, a sense of distrust from themanagement of the regional executive Board of Hanura Political Party in West Sumatera towards OsmanSapta Odang. Secondly, the Chief of Regional Executive Board of Hanura Political Party in WestSumatera was disappointed about Wiranto's inability to take an outright stance regarding the conflictsthat occurred in the management. Thirdly, a lack of mutual respect between senior and junior figures ofthe Hanura Political Party in West Sumatera. Fourthly, different opinions about party managementbetween Osman Sapta Odang's side and Daryatmo's side. The political conflict in Hanura hasimplications for the replacement of the chairman of the Regional Representative Council of the Republicof Indonesia and the dismissal of 10 Hanura Political Party members from the Regional House ofRepresentatives in West Sumatera, who are on Daryatmo's side; therefore the dismissed cadres chose toswitch parties.